1995
DOI: 10.1364/ao.34.001081
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric seeing measurements on Mt Wilson: power spectra and outer scales

Abstract: We have measured power spectra of atmospheric phase fluctuations with the Mark III stellar interferometer on Mt. Wilson under a wide variety of seeing conditions. On almost all nights, the high-frequency portions of the temporal power spectra closely follow the form predicted by the standard Kolmogorov-Tatarski model. At lower frequencies, a variety of behavior is observed. On a few nights, the spectra clearly exhibit the low-frequency flattening characteristic of turbulence with an outer-scale length of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 15 publications
7
43
1
Order By: Relevance
“…V obs (t c ; p) is insensitive to scintillation (Buscher et al 1995), variable extinction, and variable detector efficiency because they affect I sig 0 (t f ; p) and I sig 12 (t f ; p) in the same manner. However, the variability of K(t c ), due to variable seeing and fringe/angletracking errors (Paper I), adversely affects V obs (t c ; p).…”
Section: The V Obs Observv Ablementioning
confidence: 99%
“…V obs (t c ; p) is insensitive to scintillation (Buscher et al 1995), variable extinction, and variable detector efficiency because they affect I sig 0 (t f ; p) and I sig 12 (t f ; p) in the same manner. However, the variability of K(t c ), due to variable seeing and fringe/angletracking errors (Paper I), adversely affects V obs (t c ; p).…”
Section: The V Obs Observv Ablementioning
confidence: 99%
“…Considering the von-Karman model, it can be shown that the theoretical temporal power spectrum of the OPD fluctuations (Buscher et al 1995; can be divided into different cases as plotted in Fig. C.1: -At very low frequencies, f < f 0 = v/L 0 where v is the average wind speed, the spectrum flattens to a f 0 power law as the result of the finite outer scale; -At low frequency, f 0 < f < f 1 = 0.2v/B, the conventional Kolmogorov f −2/3 law holds.…”
Section: Appendix B: Others Factors Reducing the Fringe Visibilitymentioning
confidence: 99%
“…Following Buscher (1995), the coherence time t 0 can be deduced from the vertical position of the f −8/3 asymptote of the power spectrum W Φ , since:…”
Section: Appendix B: Others Factors Reducing the Fringe Visibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Optical interferometry is limited by the spatial and temporal dimensions of atmospheric turbulence, characterized by r 0 , the coherence length defined by Fried [4] and t 0 , the atmospheric coherence time (we adopt the definition advocated by Buscher [5]). Once the collecting aperture or the integration time exceeds a few times r 0 or t 0 , the interference fringe signal-to-noise ratio S begins to decrease.…”
Section: Introductionmentioning
confidence: 99%